Health services for linguistic minorities in a bilingual setting: Challenges for bilingual professionals - Drolet, Marie; Savard, Jacinthe; Benoît, Josée; Arcand, Isabelle; Savard, Sébastien; Lagacé, Josée; Lauzon, S.; Dubouloz, Claire-Jehanne (Qualitative Health Research, 2014)
We explore in this qualitative research the challenges faced by bilingual health and social services professionals in a Canadian bilingual setting, as well as the strategies used to overcome them. Eight focus groups were conducted with a total of 43 bilingual Francophone professionals who offered services in French in 21 health and social service organizations in eastern Ontario, Canada. We highlight linguistic issues affecting a minority Francophone clientele, the shortage of services in French, and organizational issues within these agencies. The solutions that the professionals adopt for better serving the clients and overcoming these challenges focus on adapting services from linguistic angles. In the long term, such an enhanced approach can affect staff well-being. Ensuring access to services for linguistic minority populations and the active offer of same should not rest solely on the shoulders of such professionals, but rather on organizational strategies.

Issues and challenges in providing services in the minority language: The experience of bilingual professionals in the health and social service network - de Moissac, Danielle; Drolet, Marie; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette; Benoît, Josée; Arcand, Isabelle; Lagacé, Josée; Dubouloz, Claire-Jehanne (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
This chapter explores the experience of bilingual professionals with the provision of health and social services in the official language of minority communities in Canada. Seventy-two professionals from Manitoba and eastern Ontario describe the main issues associated with language access, and the challenges with which they are faced in their day-to-day responsibilities with the active offer of these services. Professionals reported challenges such as shortage of bilingual professionals and services, and difficulty identifying clients who wish for services in the official language of the minority and finding bilingual professionals, as well as lack of organizational support to actively offer services in the minority language in health facilities. Some suggestions to better support the practice of active offer are provided. Key Words: active offer, health and social services, official language, minority communities, professionals.
Chapter 8

Enjeux et défis dans l’offre de services dans la langue de la minorité : l’expérience des professionnels bilingues dans le réseau de la santé et des services sociaux - de Moissac, Danielle; Drolet, Marie; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette; Benoît, Josée; Arcand, Isabelle; Lagacé, Josée; Dubouloz, Claire-Jehanne (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
Le présent chapitre dévoile l’expérience de professionnels bilingues quant à l’offre de services sociaux et de santé dans la langue officielle de la minorité en contexte canadien. Soixante-douze professionnels du Manitoba et de l’Est ontarien décrivent les principaux enjeux associés à la langue et les défis auxquels ils sont confrontés quotidiennement dans l’offre active de ces services. Ces défis concernent la pénurie de professionnels et de services bilingues, la difficulté à repérer le client désirant un service dans la langue officielle de la minorité et les professionnels bilingues, ainsi que l’absence d’appui organisationnel pour faire une offre active de services dans les établissements de santé. Pour mieux soutenir l’offre de services dans la langue de la minorité, des pistes de solution sont proposées. Mots-clés : offre active, santé et services sociaux, langue officielle, contexte minoritaire, professionnels.
Chapitre 8